ANALISIS DETERMINAN TERHADAP AGRESIVITAS PAJAK: (Studi pada perusahaan LQ 45) - Puji Lestari, Mela; Siti Aliyah (JAE (JURNAL AKUNTANSI DAN EKONOMI), 2022)
This study aims to analyze the factors that affect tax aggressiveness in LQ-45 companies listed on the Indonesia Stock Exchange for the 2018-2020 period. The type of data in this study is quantitative data. This study uses secondary data from the LQ45 company annual report for the 2018-2020 period. The sampling technique used is purposive sampling, namely the technique of determining the sample with certain considerations/criteria. The data analysis method used is multiple regression analysis, classical assumption test, and hypothesis testing. The results of this study indicate that company size, capital intensity and positive influence on tax aggressiveness in LQ45 companies.